2021
DOI: 10.3389/fpls.2021.715436
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer Regulated Grain Storage Protein Synthesis and Reduced Chalkiness of Rice Under Actual Field Warming

Abstract: Our previous study has shown that nitrogen plays an important role in dealing with significantly increased chalkiness caused by elevated temperature. However, the role of nitrogen metabolites has not been given sufficient attention, and its regulatory mechanism is not clear. This study investigated the effects of high temperature and nitrogen fertilizer on the synthesis of grain storage protein and further explored the quality mechanism under the actual scenario of field warming. Results showed that increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…This might be due to the different timing and management of nitrogen application (Zhu et al, 2016(Zhu et al, , 2017Zhao et al, 2020;Hu et al, 2021;Ning et al, 2021). A slight improvement in appearance quality in lines with highly expressed Wx alleles was observed with increased nitrogen at higher temperatures, which was consistent with a previous report (Wang et al, 2021). However, this decrease in CR and CD was not found at LT (Figures 3D-F, 5B and Table 3), suggesting the pivotal role of HTs and mutual effect among temperature, nitrogen fertilization, and Wx genotype on chalkiness formation.…”
Section: Nitrogen Fertilization and Temperature Affect Quality Differ...supporting
confidence: 90%
See 1 more Smart Citation
“…This might be due to the different timing and management of nitrogen application (Zhu et al, 2016(Zhu et al, , 2017Zhao et al, 2020;Hu et al, 2021;Ning et al, 2021). A slight improvement in appearance quality in lines with highly expressed Wx alleles was observed with increased nitrogen at higher temperatures, which was consistent with a previous report (Wang et al, 2021). However, this decrease in CR and CD was not found at LT (Figures 3D-F, 5B and Table 3), suggesting the pivotal role of HTs and mutual effect among temperature, nitrogen fertilization, and Wx genotype on chalkiness formation.…”
Section: Nitrogen Fertilization and Temperature Affect Quality Differ...supporting
confidence: 90%
“…However, this decrease in CR and CD was not found at LT (Figures 3D-F, 5B and Table 3), suggesting the pivotal role of HTs and mutual effect among temperature, nitrogen fertilization, and Wx genotype on chalkiness formation. It is generally agreed that HT induces the formation of chalky grains and reduces appearance and milling qualities (Counce et al, 2005;Zhang et al, 2016;Wang et al, 2021;. In the present study, we found that both CR and CD were higher under the higher temperature conditions and transparency decreased (Figures 4A,I-K).…”
Section: Nitrogen Fertilization and Temperature Affect Quality Differ...supporting
confidence: 72%
“…Whether globulin is involved in the regulation of seed development is still unclear. Previously, it has been reported that protein content is negatively correlated with grain chalkiness [ 21 , 22 , 23 ]. The negative correlation between globulin content and chalkiness was also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon and nitrogen metabolisms are crucial to both the yield and quality of rice grains, and their products contained in starch and proteins account for nearly 87% of the dry matter in brown rice [16]. Nitrogen is a crucial nutrient, and applying nitrogen fertilizers is an important management factor that affects both grain yield and quality [17][18][19]. However, more than 50% of nitrogen fertilizers applied to the field have not been absorbed and utilized by crops and consequently cause soil acidification and environmental pollution, which seriously threaten humans' health [20].…”
Section: Introductionmentioning
confidence: 99%